Raising native bees: an agroecological pedagogy with roots - Yorlis Luna; Elda Miriam Aldasoro Maya; Eric Vides Borrel; Helda Morales; Peter Rosset (Revista Brasileira de Educação do Campo, 2022)
There is a general consensus on the need for agroecological scaling up as an alternative to the crisis generated by the unsustainability of the industrial agriculture model and even more so in the current context of a health pandemic. However, the transition from conventional to agroecological production is a theoretical, methodological and practical challenge, since it implies generating lasting changes in the thoughts, feelings and actions of human beings. In this paper we explore how the breeding of native bees favors the learning of agroecology in Nicaragua. The breeding of native bees is an ancestral practice in Nicaragua, however, it is at risk due to landscape degradation and cultural changes. Through participatory action-research in the department of Carazo, we document how the demands of meliponiculture become motivating elements for advancing agroecological principles. Learning to raise native stingless bees is a slow, daily, active process that changes individuals and the landscape. This work identifies the way in which an element of the territory itself becomes a device that favors agroecological change, in correspondence with local knowledge, spirituality and culture.